Private Equity in Transition: Co-Investments, ESG Integration and Digitalisation as Key Strategies for German SMEs - Norman SCHERER (Communications of International Proceedings, 2023)
Amidst economic uncertainties and geopolitical tensions, traditional debt financing instruments in the real estate and project development industry are losing appeal, leading to a surge in private equity (PE) as a promising financing alternative. This study examines the increasing significance of PE co-investment funds as financial instruments in an evolving market environment. Drawing from primary sources, including market data from Morningstar, Pitchbook, European Central Bank, and other referenced studies, the analysis sheds light on the reduced transaction activity of private equity in 2023 and the consequent adaptation strategies, such as the emergence of "continuation vehicles" and the pivotal role of co-investments. Additionally, a deep dive into Germany's SME landscape reveals the transformative potential of PE in supporting businesses, particularly through the integration of ESG (environmental, social and governance) parameters and the promotion of digitalization. Through qualitative analysis and comprehensive data collection from both primary and secondary sources, the study underscores the fundamental role of private equity in the current business scenario, enabling companies to navigate challenges and implement vital transformations.
Keywords: Private equity; co-investment funds; transaction activities; ESG; SME